PEMBINAAN PELAKU USAHA BUBUR ASE UNTUK MENGEMBANGKAN WISATA KULINER DI DKI JAKARTA - Liliana Dewi; Shofi Dhiya Ulhaq (Bajang Institute, 2022)
The objective is to find out what forms of guidance the Creative Economy Development section of Disparekraf DKI Jakarta to provides to the local entrepreneur of Bubur Ase, The location of this qualitative research is DKI Jakarta. This research took three resource persons involved in the coaching activities: the interview, observation, and documentation techniques—the training for the Bubur Ase local entrepreneur. The results of the interviews were then analyzed using a SWOT analysis. The results obtained from this research are that the Creative Economy Development section of Disparekraf DKI Jakarta acts as a motivator, facilitator and dinamysator to develop human resources of Bubur Ase’s entrepreneur through Jakpreneur program. In this coaching activity, there are still some obstacles in developing human resources.